E. H. Sothern papers. - Sothern, E. H. (Edward Hugh), 1859-1933.
Four ALS (1919, 1928, undated) written by Sothern; ALS (1914 January 5) written by his wife, actress Julia Marlowe; typescript description of a World War I battle; and notebook containing handwritten copies of poems and recitations read by Sothern to soldiers serving on the front lines of the war.
Actor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Marlowe, Julia, -- 1865-1950 -- Correspondence; World War, 1914-1918 -- Campaigns; World War, 1914-1918 -- Theater and the war; Actors